Metacognitive Profile of Students Who Play Chess in Solving Mathematics Problems - Bahri, Syaiful; Noviani, Julia; Kurniawati, Annisa Dwi (Juring (Journal for Research in Mathematics Learning), 2023)
Mathematics is the study of patterns, so in chess pattern recognition is very important in problem solving. Chess is a problem-solving instrument and the best way to analyze problem-solving because chess has clear rules in decision making, thus a skilled chess player becomes a good problem solver. Metacognitive activity and problem-solving processes are intimately intertwined. The purpose of this research is to describe the metacognition profiles of students who play chess and students who do not play chess in solving mathematical problems. This research is a qualitative-research. The research subjects in this study were students who could play chess and students who could not play chess. The criteria are students who have participated in chess matches as low as possible at the sub-district level and regularly play chess, while students who cannot play chess are students who do not understand the basics of playing chess. This research carried out in class VIII at a junior high school in Surabaya. The instruments in this study were math ability tests, problem-solving tests and interview guidelines. The data collection procedure was carried out by giving students a math problem-solving test and interviews. The data analysis technique in this study was carried out in the following steps; transcribing the subject's answers, examining the subject's answer data from interviews, data reduction, data categories, analyzing students' metacognition profiles, and drawing conclusions. The results of the study stated that the metacognitive abilities in solving problems of chess students were better than those of non-chess students. The ES subject achieved 80% of metacognitive activity indicators, while the MI subject only achieved 54.25% of metacognitive activity indicators.